Food technology : applied research and production techniques - Meghwal, Murlidhar; Goyal, Megh Raj; Kaneria, Mital J. (Apple Academic Press Inc., 2018)
"In this era of climate change and food/water/natural resource crises, it is important that current advancements in technology are made taking into consideration the impact on humanity and the environment. This new volume, Food Technology: Applied Research and Production Techniques, in the Innovations in Agricultural and Biological Engineering book series, looks at recent developments and innovations in food technology and sustainable technologies. Advanced topics in the volume include food processing, preservation, nutritional analysis, quality control and maintenance as well as good manufacturing practices in the food industries. The chapters are highly focused reports to help direct the development of current food- and agriculture-based knowledge into promising technologies. Features:provides information on relevant technology makes suggestions for equipment and deviceslooks at standardization in food technologyexplores new and innovative packaging technologystudies antimicrobial activities in foodconsiders active constituents of foods and provides information about isolation, validation and characterization of major bioactive constituents discusses the effect of laws and regulatory guidelines on infrastructure to transform technology into highly value-added productsFood Technology: Applied Research and Production Techniques will be a very useful reference book for food technologists, practicing food engineers, researchers, professors, students of these fields and professionals working in food technology, food science, food processing, and nutrition."- Resumé vydavatel
Keywords: potraviny; potravinářská technologie; biotechnologie; foodstuffs; food technology; biotechnology; sborníky; elektronické knihy; papers of several authors; electronic books